ANALISIS HARGA POKOK PENJUALAN TERHADAP LABA KOTOR (Studi Kasus Pada Cv. Andromedia Malang) - Sudarmanto, Apong; Dianawati, Eris; Mustikowati, Rita Indah (Jurnal Riset Mahasiswa Akuntansi, 2015)
This study aimed to examine the cost of sales on gross profit in the CV. Andromedia Malang. This research is descriptive quantitative replication model. The data used in this research is secondary data. Data collection techniques in this study is the documentation and review of the literature. The variable used is the independent variable is the price of goods sold and the dependent variable is the gross profit. Cost of goods sold According to Gill and Chatton translated by Prabaningtyas (2005), is the cost of manufacture or purchase price that is attached to the product finished goods shipped from the supplier to the customer, while the gross profit according to PSAK No. 25 (2007), gross profit is the difference between net income and sales cost of goods sold. The gross profit should be analyzed to determine the development of growth experienced by the company in certain periods. Analysis of the development, is necessary in order to create optimal sales, and sales needed to generate profits. The analysis technique used is a simple regression analysis From the results of hypothesis testing that has been done, the study states that the cost of goods sold significant effect on gross profit. It is evident that the results of the statistical calculation is less than significant levels. In this study, the cost of sales positive effect on gross profit due to cost of sales and gross profit both increased, or in other words the same direction. Increase in gross profit is also proved that the company is able to maintain and even increase public confidence in the products produced by the company, in other words the company can maintain the existence in the market competition.